Geographical connections: Royal Geographical Society (with IBG) Medals and Awards ceremony 2013. Issue 3 (6th August 2013) - Rees, Judith; Palin, Michael; Richards, Keith; Jones, Kelvyn; Longley, Paul; Page, Susan
Abstract : The Royal Geographical Society (with IBG)'s annual Medals and Awards recognise achievements in the research, communication and teaching of a wide range of geographical knowledge. The speeches and citations are a record of the ceremony of 2013. With comments by Michael Palin, and Professors Keith Richards, Kelvyn Jones, Paul Longley and Susan Page, the speeches encompass travel, fluvial geomorphology, quantitative research, geographic information science and tropical peatland conservation.